Editorial - Gavilán de Labourdette, Mirta Graciela (2013)
This edition corresponds to number 13 of our annual magazine Guidance and Society. This year is particularly significant for those who make this publication possible and for all who, from different workplaces, join to our initiative and guidance projects.